2013
DOI: 10.1007/s10571-013-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Does Not Affect Memory Performance in Adult Male Rats

Abstract: Bisphenol A (BPA) is an estrogenic endocrine disruptor used for producing polycarbonate plastics and epoxy resins. This study investigated the effects of oral BPA administration on memory performance, general activity, and emotionality in adult male Sprague Dawley rats using a battery of behavioral tests, including an appetite-motivated maze test (MAZE test) used to assess spatial memory performance. In addition, in order to confirm the effects of BPA on spatial memory performance, we examined whether intrahip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As an endocrine disrupting chemical (EDC) that can bind and activate estrogen receptors, as well as other steroidogenic and non-steroidogenic receptors (Lee et al, 2003; Vandenberg et al, 2009; Wetherill et al, 2002; Xu et al, 2005; Zoeller et al, 2005), BPA exposure may negatively impact this cognitive process. Several assessments have been developed that specifically measure spatial navigational learning and memory in rodents, including the Barnes maze, Morris water maze, radial arm maze, and appetite-motivated maze tests (Barnes, 1979; Kuwahara et al, 2014; Morris, 1984; Olton, 1976; Sharma et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an endocrine disrupting chemical (EDC) that can bind and activate estrogen receptors, as well as other steroidogenic and non-steroidogenic receptors (Lee et al, 2003; Vandenberg et al, 2009; Wetherill et al, 2002; Xu et al, 2005; Zoeller et al, 2005), BPA exposure may negatively impact this cognitive process. Several assessments have been developed that specifically measure spatial navigational learning and memory in rodents, including the Barnes maze, Morris water maze, radial arm maze, and appetite-motivated maze tests (Barnes, 1979; Kuwahara et al, 2014; Morris, 1984; Olton, 1976; Sharma et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Some reports have suggested that BPA exposure impairs spatial learning and memory (Diaz Weinstein et al, 2013; Eilam-Stock et al, 2012; Goncalves et al, 2010; Jasarevic et al, 2011; Jasarevic et al, 2013; Kim et al, 2011; Kuwahara et al, 2013; Viberg et al, 2011; Xu et al, 2013); while others suggest minimal or no BPA effects on spatial navigation (Ferguson et al, 2012; Kuwahara et al, 2014; Neese et al, 2013; Ryan and Vandenbergh, 2006; Sadowski et al, 2014a; Williams et al, 2013). Differences in species, age at and/or route of exposure, BPA dose, and testing methods may account for those varying results.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fear-related behaviors were altered by BPA in mice (Matsuda et al, 2013) and rats (Negishi et al, 2004). In the elevated plus maze (EPM), exposure of rats to BPA produced anxiogenic effects (Patisaul and Bateman, 2008;Patisaul et al, 2012;Diaz Weinstein et al, 2013;Zhou et al, 2015), anxiolytic effects (Farabollini et al, 1999;Fujimoto et al, 2013;Kuwahara et al, 2014), or unclear/nonexistent effects (Negishi et al, 2004;Fujimoto et al, 2006;Jones and Watson, 2012;Kuwahara et al, 2013). The different reported effects of BPA in rats in the EPM might be due to differences in experimental design or environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The apparatus and the experimental procedures were adopted from our previous study (Kuwahara et al, 2014). The apparatus (Fig.…”
Section: Maze Testmentioning
confidence: 99%
“…The effective dose of NP, from a neurobehavioral standpoint, is much lower than the dosage associated with general toxicity (Negishi et al, 2004). Our present study was, therefore, designed to evaluate the effects of oral exposure to low dose of NP on learning and memory performance, general activity levels, and emotionality in male and female Sprague-Dawley (SD) rats using a battery of behavioral tests, including a series of learning performance tests previously used in our laboratory (Kuwahara et al, 2014). To our knowledge, this is the first study investigating the effects of oral NP administration on CNS in male and female rats.…”
Section: Introductionmentioning
confidence: 99%